Essay writing of English FAL Rural Learners in Mopani West District, Limpopo Province : an analysis - Mailula, Maphefo Rebecca (University of Limpopo, 2021)
The study explored essay writing errors of English First Additional Language (EFAL) FET rural learners. The aim of the study was to analyse essay writing errors of the EFAL FET learners in rural schools. EFAL Grade 11 learners together with their educators from 4 circuits in Mopani West District of Limpopo Province (LP), South Africa (SA), participated in the study. The learners’ 40 essays were analysed. Additionally, the learners and educators were interviewed and the data generated were analysed. A qualitative Content Analysis (CA) research method was used to collect data. The sample was made up of 3 instruments; an essay checklist for the 40 essays, EFAL learners’ group interviews that consisted of 4 equal groups made up of 10 learners per school, and interviews with 4 educators from each of the school represented. N – Vivo was used for data transcription, storage and analysis. Errors populated in the checklist were arranged into smaller units, identified, analysed, described and reported. Data obtained through semi-structured interviews with EFAL learners and educators were transcribed and analysed thematically. The analysis of the EFAL FET rural learners’ essay writing errors revealed weaknesses pertaining to choice of essay topics, proofreading, spelling, punctuation and grammar.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2021
Keywords: English First Additional Language; Rural Learners; Mopani West District; Essay -- Authorship; Basic writing (Remedial education); English language -- Writing